Waste Management during the COVID-19 Pandemic - United Nations Environment Programme (United Nations, 2020)
The report reviews the existing practices of healthcare waste management under the COVID-19 (coronavirus) pandemic and to identify best available or appropriate waste management practices that are operationally and technically in line with local conditions. The report considers various approaches, identifies best practices and technologies, and provides recommendations for policy-makers and practitioners to improve waste management during the COVID-19. Drawing insight from numerous consultations, the report gives particular attention to developing countries and cities, which may already lack adequate waste management.